2007
DOI: 10.5424/sjar/2007052-245
|View full text |Cite
|
Sign up to set email alerts
|

Short communication. Integration of emergence and population dynamic models for long term weed management using wild oat (Avena fatua L.) as an example

Abstract: Weed emergence models and weed population models have shown to be important tools for decision making. However, there have been no attempts to integrate a weed emergence model with a population dynamics model to build an improved model with increased predictive capacity. In this paper, a method of integrating both types of model is presented and an application building a mathematical model based on previously reported seedling emergence and population dynamics data to simulate cohort-dependent population dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Furthermore, the model can give information about the predicted density of seedlings, if there are data on the actual non‐dormant seed bank densities that can be obtained from soil seed bank analyses. Further information about weed density dynamics can also be obtained by integrating the model with population dynamic models (González‐Díaz et al ., )…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the model can give information about the predicted density of seedlings, if there are data on the actual non‐dormant seed bank densities that can be obtained from soil seed bank analyses. Further information about weed density dynamics can also be obtained by integrating the model with population dynamic models (González‐Díaz et al ., )…”
Section: Discussionmentioning
confidence: 99%
“…Chantre et al (2012) reported that the Weibull model was deemed to provide a better fit than the other models for A. fatua seedling emergence in Argentina. However, Gonzalez-Diaz et al (2007) reported that the Logistic model was deemed to provide a better fit than the other models for A. fatua seedling emergence in Spain. The differences between A. fatua and D. sophia emergence patterns in semiarid conditions might be attributed mainly to a highly unpredictable precipitation regime, fuctuating thermal environment and seed dormancy level variations (Chantre et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already been carried out to assess the long-term population behavior of different weed species, including Lolium rigidum [5][6][7]. To the best of our knowledge, there are no studies of this kind on L. multiflorum.…”
Section: Introductionmentioning
confidence: 99%